Unexpected drug residuals in human milk in Ankara, capital of Turkey - Ayşe Meltem Ergen; Sıddıka Songül Yalçın (BMC, 2019)
Abstract Background Breast milk is a natural and unique nutrient for optimum growth and development of the newborn. The aim of this study was to investigate the presence of unpredictable drug residues in mothers' milk and the relationship between drug residues and maternal-infant characteristics. Methods In a descriptive study, breastfed infants under 3 months of age and their mothers who applied for child health monitoring were enrolled for the study. Information forms were completed for maternal-infant characteristics, breastfeeding problems, crying and sleep characteristics of infants. Maternal and infant anthropometric measurements and maternal milk sample were taken. Edinburgh Postpartum Depression Scale was applied to mothers. RANDOX Infiniplex kit for milk was used for residual analysis. Results Overall, 90 volunteer mothers and their breastfed infants were taken into the study and the mean age of the mothers and their infants was 31.5 ± 4.2 years and 57.8 ± 18.1 days, respectively. Anti-inflammatory drug residues in breast milk were detected in 30.0% of mothers and all had tolfenamic acid. Overall, 94.4% had quinolone, 93.3% beta-lactam, 31.1% aminoglycoside and 13.3% polymycin residues. Drugs used during pregnancy or lactation period were not affected by the presence of residues. Edinburgh postpartum depression scores of mothers and crying and sleeping problems of infants were similar in cases with and without drug residues in breast milk. When controlling confounding factors, maternal body mass index alterations were detected to be significantly lower in mothers with anti-inflammatory drug residues in breast milk than in their counterparts (p = 0.017). Conclusions Our study suggests that there are unpredictable drug residues in the milk of many mothers. Anti-inflammatory drug exposure might affect maternal weight change during the postpartum period. Further studies are required to evaluate the impact of drug residues on maternal and infant health.